Smoking and the risk of prostate cancer in the European Prospective Investigation into Cancer and Nutrition - Rohrmann, Sabine; Linseisen, Jakob; Kaaks, Rudolf; Teucher, Birgit (British journal of cancer, 2013)
BACKGROUND: Smoking is not associated with prostate cancer incidence in most studies, but associations between smoking and fatal prostate cancer have been reported. METHODS: During 1992 and 2000, lifestyle information was assessed via questionnaires and personal interview in a cohort of 145,112 European men. Until 2009, 4623 incident cases of prostate cancer were identified, including 1517 cases of low-grade, 396 cases of high grade, 1516 cases of localised, 808 cases of advanced disease, and 432 fatal cases. Multivariable Cox proportional hazards regression models were used to examine the association of smoking status, smoking intensity, and smoking duration with the risk of incident and fatal prostate cancer. RESULTS: Compared with never smokers, current smokers had a reduced risk of prostate cancer (RR=0.90, 95% CI: 0.83-0.97), which was statistically significant for localised and low-grade disease, but not for advanced or high-grade disease. In contrast, heavy smokers (25+ cigarettes per day) and men who had smoked for a long time (40+ years) had a higher risk of prostate cancer death (RR=1.81, 95% CI: 1.11-2.93; RR=1.38, 95% CI: 1.01-1.87, respectively). CONCLUSION: The observation of an increased prostate cancer mortality among heavy smokers confirms the results of previous prospective studies.